Preparation method of antibacterial, fresh-keeping and oil-proof starch film based on nanocellulose immobilized enzyme
By using nanocellulose immobilized enzyme in starch film, the shortcomings of starch-based films in mechanical strength, water resistance, antibacterial properties and fresh preservation ability were solved, and starch films with excellent performance were prepared, satisfying the food packaging industry The need for safety, health and efficient preservation.
Patent Information
- Application Number
- CN202411555088.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-07
AI Technical Summary
The existing starch-based films have shortcomings in mechanical strength, water resistance, antibacterial properties and fresh preservation capabilities, which are difficult to meet the needs of modern food packaging industry for safety, health and efficient fresh preservation.
Using a nanocellulose immobilization enzyme-based method, the prolulanase was immobilized by cellulose nanofiber filaments and added tannin acid to regulate the performance of the starch film and impart its antibacterial and fresh-preserving properties.
The prepared starch film has excellent mechanical properties, antibacterial properties and fresh preservation properties, which significantly improves the oil resistance and corrosion resistance of starch-based films, and meets the food packaging industry's demand for efficient fresh preservation.
Smart Images

Figure CN119391027A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of food, and in particular to a method for preparing an antibacterial, fresh-keeping and oil-proof starch film based on nanocellulose immobilized enzyme. Background Art
[0002] Starch is generally considered to be a biodegradable material with development potential due to its abundant reserves, low price, good plasticity, and safe use. However, in actual applications, the large number of hydroxyl groups naturally present in starch and the large amount of plasticizers added during the material preparation process (such as glycerol, polyethylene glycol, etc.) will make starch products easily absorb moisture from the environment, causing the related products to collapse and deform, and the mechanical properties to deteriorate, seriously affecting their use value. Therefore, how to reduce the hydrophilicity of the material and broaden the use scenarios of its products has become a core key issue that needs to be urgently solved in the application of starch materials.
[0003] In order to improve the moisture resistance and water resistance of starch-based materials, various mixing, synthesis and coating technologies have been developed, such as mixing with fats or oils, mixing with proteins / gelatin, using mineral fillers, cellulose fibers, polysaccharide-based particles and self-reinforcement technology to enhance their performance. However, it is difficult to change the hydrophilicity of starch-based mixed materials by directly mixing with hydrophobic substances, and phase separation often occurs, and it is difficult to exert the advantages of each material; unless the starch content is low enough, the hydrophobic polymer forms a separate phase in the mixture, and the starch is only used as a filler. On the other hand, chemical fillers such as various nanofillers are added to improve the performance of starch-based materials, but nanofillers such as titanium oxide, zinc oxide, silicon oxide, etc. are not only expensive, but also pollute the environment, are not suitable for food packaging applications, and are harmful to human health. In addition, starch cross-linking technology requires mixing the cross-linking agent with the starch suspension during the production process, and then casting it into a film. This method is not suitable for industrial manufacturing because starch film materials are mainly produced by extrusion casting in industry. The surface coating method has the advantages of easy processing, low cost, flexible thickness control, and maximization of the natural properties of the base material, which is beneficial to the post-processing of starch film materials.
[0004] Chinese invention patent application 201810982787.4 discloses a method for preparing a nano starch super hydrophobic coating, specifically including the following steps: first using ultrasonic treatment starch, preparing nano starch dispersion; secondly, the nano starch dispersion is surface treated with a silane coupling agent containing a double bond; again, the surface treated nano starch is polymerized with vinyl acetate emulsion to synthesize a hydrophobic emulsion; finally, the emulsion is dip-coated on the substrate surface, and a super hydrophobic coating is obtained by drying. The nano material used in the method of the present invention is starch, and low surface energy material is polyvinyl acetate, and the materials used are low in cost and easy to obtain, with good environmental performance, and the coating prepared using the method has good super hydrophobic performance, and the contact angle of water exceeds 151.6 °. The Chinese invention patent application 2018109634937 discloses a method for preparing a photocurable nanocellulose / AESO emulsion, which includes the following steps: (1) dispersing nanocellulose in deionized water, stirring magnetically for 1 hour at room temperature, and preparing a nanocellulose suspension; (2) adding a photoinitiator Darocure 1173 to epoxy soybean oil acrylate, stirring magnetically for 10 minutes at room temperature, and preparing an AESO oil phase; (3) mixing the AESO oil phase and the nanocellulose suspension in a mass ratio of 1:1 to 1:5, and emulsifying at high speed at room temperature, with an emulsification rate of 5000r / min to 15000r / min and an emulsification time of 5min to 10min, to prepare a photocurable nanocellulose / AESO emulsion. The present invention does not require the addition of any surfactant to obtain a photocurable nanocellulose / AESO emulsion with good stability. The emulsion combines the degradable properties of nanocellulose and AESO, and can be rapidly cured under UV light to form a film layer with good hydrophobicity and gas barrier properties.
[0005] Therefore, how to effectively compound matrices of different properties and give full play to the advantages of each component is the key to solving the current problems of starch films in mechanical strength, water resistance, antibacterial properties and preservation ability. This is of great significance to promoting the development of food storage and preservation technology in my country and providing new packaging materials. Summary of the invention
[0006] The present invention aims to solve the above technical problems and provides a method for preparing an antibacterial, fresh-keeping and oil-proof starch film based on nanocellulose immobilized enzyme.
[0007] In order to solve the above technical problems, the technical solution provided by the present invention is:
[0008] A method for preparing an antibacterial, fresh-keeping and oil-proof starch film based on nanocellulose immobilized enzyme comprises the following steps:
[0009] S1. Preparation of antimicrobial agent:
[0010] Mix citronellol, anthocyanin, chitosan, cinnamyl alcohol and menthol together, add starch, nano silver particles and quaternary ammonium salt in 2-3 times and mix together to obtain an antibacterial agent;
[0011] S2. Preparation of mixture A:
[0012] Absolutely dry starch and cationic starch are prepared into an aqueous solution of a certain concentration, heated in a 75°C water bath for gelatinization, polyvinyl alcohol is added and continued to be heated and stirred until completely dissolved, folic acid is added to the solution and reacted for 30 minutes, α-amylase is added to the solution and mixed evenly to obtain a mixture A, and the mixture A is divided into three parts;
[0013] S3. Preparation of cellulose nanofibril immobilized pullulanase:
[0014] Take CNF, the mass of which is 1.0%-10% of the mass of absolute dry starch, take pullulanase, the amount of which is 1U-10U per gram of absolute dry starch, mix CNF and pullulanase, and adjust the mixture with phosphate buffer to a pH value of 6, and shake the mixture with the adjusted pH value at a constant speed of 100-300rpm in a constant temperature air bath shaker at 30°C for 1-3 hours to complete the immobilization of pullulanase on cellulose nanofibrils, and obtain Pul@CNF complex;
[0015] S4, cellulose nanofibril immobilized pullulanase system enzymatically hydrolyzes starch and adds tannic acid:
[0016] Place the absolutely dry starch in a 250ml three-necked flask or a round-bottomed flask, add 50ml of distilled water to the flask, and place the flask in a 38°C water bath. Stir slowly to fully disperse the starch, and continue stirring for 5 minutes. Add the Pul@CNF complex prepared in step 1 and two portions of mixture A to the dispersed starch solution, and add water to a total volume of 100ml. Then slowly add tannic acid to the solution, continue stirring for 10 minutes, and heat to 95°C at a rate of 1°C / min. When the temperature reaches 95°C, add a plasticizer accounting for 40% of the absolute dry starch mass to the solution, and keep warm for 30 minutes while stirring. After stirring, remove bubbles from the obtained starch solution, and use a casting method to evenly spread the starch solution on an acrylic plate. Place the acrylic plate with the spread starch solution in a 50°C oven and dry for 8 hours.
[0017] S5, antibacterial coating:
[0018] After drying is completed, the composite starch film is torn off from the acrylic plate, MC and HPMC are dissolved in ethanol, heated to 65°C, and then PEG, epoxy soybean oil acrylate and water are slowly added to form a uniform transparent coating solution or gel, an antibacterial agent and a portion of mixture A are added to the coating solution or gel, and the coating solution or gel is applied to the composite starch film using a glass roller, and stored at a temperature of 25°C and a relative humidity of 50% for 48 hours to obtain a composite starch film containing curcumin.
[0019] Preferably, the pH value of the phosphate buffer is 4-7.
[0020] Preferably, the mass ratio of the starch to the antibacterial agent is 1:3.
[0021] Preferably, the ratio of the absolute dry starch to the cationic starch is 1:1.
[0022] Preferably, the added amount of the tannic acid is 1%-20%.
[0023] Preferably, the cellulose nanofibrils are one or any combination of anionic, cationic, and neutral cellulose nanocrystals.
[0024] Preferably, the plasticizer is one or any combination of glycerol, urea, ethylene glycol, polyethylene glycol, propylene glycol, sorbitol, and ethanolamine.
[0025] Preferably, the ratio of citronellol, anthocyanidin, chitosan, cinnamyl alcohol and menthol is 1-2:3-4:1-2:0.5-1:1-1.5.
[0026] Preferably, the antibacterial agent and one portion of mixture A account for 1-10% of the total amount.
[0027] After adopting the above method, the present invention has the following advantages:
[0028] The present invention discloses a method for regulating the performance of starch film by synergistically combining nanocellulose fibril-immobilized enzyme and tannic acid and imparting antibacterial and fresh-keeping properties to the film. The core of the present invention is to innovatively combine the reinforcing effect of nanocellulose fibrils, the precise catalytic effect of enzymes and the natural antibacterial properties of tannic acid, which act together on the starch matrix to prepare a starch-based film having both high amylose content and excellent mechanical properties and antibacterial and fresh-keeping functions.
[0029] The starch film of the present invention has good performance, good oil resistance, strong antiseptic performance and good antibacterial and fresh-keeping performance, and an innovative method of giving it significant antibacterial and fresh-keeping properties. In view of the deficiencies of existing starch-based films in mechanical strength, water resistance, antibacterial performance and fresh-keeping ability, the present invention proposes an efficient and environmentally friendly solution, aiming to prepare a starch-based film with excellent performance and diverse functions to meet the urgent needs of the modern food packaging industry for safety, health and efficient preservation.
[0030] The above summary is for illustrative purposes only and is not intended to be limiting in any way. In addition to the illustrative aspects, embodiments and features described above, further aspects, embodiments and features of the present invention will be readily apparent by reference to the accompanying drawings and the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or technical descriptions will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1 This is the antibacterial test diagram of the composite membrane against Escherichia coli and Staphylococcus aureus;
[0033] Figure 2 This is the oil-proof grade diagram of composite starch film;
[0034] Figure 3 This is a picture showing the preservation of cherry tomatoes using the composite film. DETAILED DESCRIPTION
[0035] Specific embodiments of the present invention will now be mentioned in detail. Although the present invention is described in conjunction with these specific embodiments, it should be appreciated that it is not intended to limit the present invention to these specific embodiments. On the contrary, these embodiments are intended to cover substitutions, changes or equivalent embodiments that may be included in the spirit and scope of the invention defined by the claims. In the following description, a large number of specific details are set forth in order to provide a comprehensive understanding of the present invention. The present invention can be implemented without some or all of these specific details. In other cases, in order not to make the present invention unnecessarily obscure, well-known process operations are not described in detail.
[0036] When used in conjunction with "including," "methods comprising," or similar language in this specification and the appended claims, the singular forms "a," "an," and "the" include plural references unless the context clearly dictates otherwise. Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs.
[0037] The present invention is further described in detail below in conjunction with the full text.
[0038] Combined with Figure 1-Figure 3 A method for preparing an antibacterial, fresh-keeping and oil-proof starch film based on nanocellulose immobilized enzyme comprises the following steps:
[0039] S1. Preparation of antimicrobial agent:
[0040] Mix citronellol, anthocyanin, chitosan, cinnamyl alcohol and menthol together, add starch, nano silver particles and quaternary ammonium salt in 2-3 times and mix together to obtain an antibacterial agent;
[0041] S2. Preparation of mixture A:
[0042] Absolutely dry starch and cationic starch are prepared into an aqueous solution of a certain concentration, heated in a 75°C water bath for gelatinization, polyvinyl alcohol is added and continued to be heated and stirred until completely dissolved, folic acid is added to the solution and reacted for 30 minutes, α-amylase is added to the solution and mixed evenly to obtain a mixture A, and the mixture A is divided into three parts;
[0043] S3. Preparation of cellulose nanofibril immobilized pullulanase:
[0044] Take CNF, the mass of which is 1.0%-10% of the mass of absolute dry starch, take pullulanase, the amount of which is 1U-10U per gram of absolute dry starch, mix CNF and pullulanase, and adjust the mixture with phosphate buffer to a pH value of 6, and shake the mixture with the adjusted pH value at a constant speed of 100-300rpm in a constant temperature air bath shaker at 30°C for 1-3 hours to complete the immobilization of pullulanase on cellulose nanofibrils, and obtain Pul@CNF complex;
[0045] S4, cellulose nanofibril immobilized pullulanase system enzymatically hydrolyzes starch and adds tannic acid:
[0046] Place the absolutely dry starch in a 250ml three-necked flask or a round-bottomed flask, add 50ml of distilled water to the flask, and place the flask in a 38°C water bath. Stir slowly to fully disperse the starch, and continue stirring for 5 minutes. Add the Pul@CNF complex prepared in step 1 and two portions of mixture A to the dispersed starch solution, and add water to a total volume of 100ml. Then slowly add tannic acid to the solution, continue stirring for 10 minutes, and heat to 95°C at a rate of 1°C / min. When the temperature reaches 95°C, add a plasticizer accounting for 40% of the absolute dry starch mass to the solution, and keep warm for 30 minutes while stirring. After stirring, remove bubbles from the obtained starch solution, and use a casting method to evenly spread the starch solution on an acrylic plate. Place the acrylic plate with the spread starch solution in a 50°C oven and dry for 8 hours.
[0047] S5, antibacterial coating:
[0048] After drying is completed, the composite starch film is torn off from the acrylic plate, MC and HPMC are dissolved in ethanol, heated to 65°C, and then PEG, epoxy soybean oil acrylate and water are slowly added to form a uniform transparent coating solution or gel, an antibacterial agent and a portion of mixture A are added to the coating solution or gel, and the coating solution or gel is applied to the composite starch film using a glass roller, and stored at a temperature of 25°C and a relative humidity of 50% for 48 hours to obtain a composite starch film containing curcumin.
[0049] The pH value of the phosphate buffer is 4-7.
[0050] The mass ratio of the starch to the antibacterial agent is 1:3.
[0051] The ratio of the absolute dry starch to the cationic starch is 1:1.
[0052] The added amount of the tannic acid is 1%-20%.
[0053] The cellulose nanofibrils are one or any combination of anionic, cationic, and neutral cellulose nanocrystals.
[0054] The plasticizer is one or any combination of glycerol, urea, ethylene glycol, polyethylene glycol, propylene glycol, sorbitol, and ethanolamine.
[0055] The ratio of citronellol, anthocyanidin, chitosan, cinnamyl alcohol and menthol is 1-2:3-4:1-2:0.5-1:1-1.5.
[0056] The antibacterial agent and one portion of mixture A account for 1-10% of the total amount.
[0057] α-Amylase is an internal enzyme that can efficiently catalyze the hydrolysis of starch into shorter oligosaccharides. The combination of α-amylase and glucanase can achieve a weight reduction of 7-10%. The enzymatic hydrolysis equilibrium time of α-amylase in starch is longer, indicating that it has a higher efficiency for high-polymerization degree straight-chain starch.
[0058] Folic acid has certain antibacterial properties and can inhibit the growth of certain microorganisms, thereby extending the shelf life of food. Folic acid may improve the film-forming property and mechanical strength of the membrane by changing the surface properties or internal structure of the membrane. Folic acid is a natural biodegradable molecule that can promote the biodegradability of the membrane, help reduce environmental pollution, and ensure that the membrane can decompose naturally after use.
[0059] Embodiment 1:
[0060] A method for preparing an antibacterial, fresh-keeping and oil-proof starch film based on nanocellulose immobilized enzyme comprises the following steps:
[0061] S1. Preparation of antimicrobial agent:
[0062] Mix citronellol, anthocyanin, chitosan, cinnamyl alcohol and menthol together, add starch, nano silver particles and quaternary ammonium salt three times and mix together to obtain an antibacterial agent;
[0063] S2. Preparation of mixture A:
[0064] Absolutely dry starch and cationic starch are prepared into an aqueous solution of a certain concentration, heated in a 75°C water bath for gelatinization, polyvinyl alcohol is added and continued to be heated and stirred until completely dissolved, folic acid is added to the solution and reacted for 30 minutes, α-amylase is added to the solution and mixed evenly to obtain a mixture A, and the mixture A is divided into three parts;
[0065] S3. Preparation of cellulose nanofibril immobilized pullulanase:
[0066] Take CNF, the mass of which is 5% of the mass of absolute dry starch, take pullulanase, the dosage of which is 5U per gram of absolute dry starch, mix CNF and pullulanase, and adjust the mixture with phosphate buffer to a pH value of 6, and shake the mixture with the adjusted pH value at a constant speed of 200 rpm in a constant temperature air bath shaker at 30°C for 2 hours to complete the immobilization of pullulanase on cellulose nanofibrils, and obtain Pul@CNF composite;
[0067] S4, cellulose nanofibril immobilized pullulanase system enzymatically hydrolyzes starch and adds tannic acid:
[0068] Place the absolutely dry starch in a 250ml three-necked flask or a round-bottomed flask, add 50ml of distilled water to the flask, and place the flask in a 38°C water bath. Stir slowly to fully disperse the starch, and continue stirring for 5 minutes. Add the Pul@CNF complex prepared in step 1 and two portions of mixture A to the dispersed starch solution, and add water to a total volume of 100ml. Then slowly add tannic acid to the solution, continue stirring for 10 minutes, and heat to 95°C at a rate of 1°C / min. When the temperature reaches 95°C, add a plasticizer accounting for 40% of the absolute dry starch mass to the solution, and keep warm for 30 minutes while stirring. After stirring, remove bubbles from the obtained starch solution, and use a casting method to evenly spread the starch solution on an acrylic plate. Place the acrylic plate with the spread starch solution in a 50°C oven and dry for 8 hours.
[0069] S5, antibacterial coating:
[0070] After drying is completed, the composite starch film is torn off from the acrylic plate, MC and HPMC are dissolved in ethanol, heated to 65°C, and then PEG, epoxy soybean oil acrylate and water are slowly added to form a uniform transparent coating solution or gel, an antibacterial agent and a portion of mixture A are added to the coating solution or gel, and the coating solution or gel is applied to the composite starch film using a glass roller, and stored at a temperature of 25°C and a relative humidity of 50% for 48 hours to obtain a composite starch film containing curcumin.
[0071] Comparison example:
[0072] Control Group A group of starch films without tannic acid was prepared as a control group, and the steps were the same as above, but tannic acid, mixture A and antimicrobial agent were not added in the steps.
[0073] Example culture:
[0074] like Figure 1 As shown, Staphylococcus aureus was selected as a representative Gram-positive strain, and Escherichia coli was selected as a representative Gram-negative strain. In the experiment, 0.2 ml of a bacterial suspension with a concentration of 107 CFU / mL was added to the liquid culture medium and cultured at 37°C for 6 hours for subsequent use. Using the dilution plate method, 0.2 ml of a 100-fold diluted bacterial solution was evenly spread on the surface of the agar solid culture medium, and the starch film sample slice was placed in the center of the culture dish. After the culture dish was placed in a constant temperature incubator at 37°C for 48 hours, the diameter of the antibacterial circle was recorded to evaluate its antibacterial effect.
[0075] Example test:
[0076] According to GB / T 7714-2015 standard, the oil resistance of starch film is evaluated. Before the test, the starch film sample is cut to the specified size and ensured to be flat. The experiment is carried out in a temperature and humidity controlled environment, set at 23±2℃ and relative humidity 50±5%. During the test, a specified volume of oil is dropped onto the starch film from a height of 25cm, and it is observed whether it penetrates quickly. After 15s, check and record the diameter of the oil stain on the absorbent paper, and take a photo for backup. According to the size of the oil stain diameter, it is evaluated against the grade table in the standard. The grade range is usually from grade 1 (no oil resistance) to grade 12 (excellent oil resistance), such as Figure 2 shown.
[0077] grade Castor oil / g Toluene / mL Heptane / mL 1 96.9 0 0 2 87.2 5 5 3 77.5 10 10 4 67.8 15 15 5 58.1 20 20 6 48.5 25 25 7 38.8 30 30 8 29.1 35 35 9 19.4 40 40 10 9.7 45 45 11 0 50 50 12 0 45 55
[0078] The starch film and PE film prepared in Example 1 were respectively covered on small tomatoes under the same conditions. Figure 3 After a preset observation period, the appearance changes, moisture retention, and spoilage of the two groups of cherry tomatoes were recorded and analyzed. This objective data collection process is designed to evaluate the specific performance of the two films in food preservation.
[0079] When the present invention is specifically implemented, Figure 1-3 As shown, the starch film prepared by the technical solution of the present invention has good performance, good oil resistance, strong antiseptic performance and good antibacterial and fresh-keeping performance, and an innovative method of giving it significant antibacterial and fresh-keeping properties. In view of the deficiencies of existing starch-based films in mechanical strength, water resistance, antibacterial performance and fresh-keeping ability, the present invention proposes an efficient and environmentally friendly solution, aiming to prepare starch-based films with excellent performance and diverse functions to meet the urgent needs of the modern food packaging industry for safety, health and efficient preservation.
[0080] The present invention and its embodiments are described above, and such description is not restrictive. What is shown in the full text is only one of the embodiments of the present invention, and the actual structure is not limited thereto. In short, if ordinary technicians in the field are inspired by it, without departing from the purpose of the invention, they can design a structure and embodiment similar to the technical solution without creativity, which should belong to the protection scope of the present invention.
Claims
1. A method for preparing an antibacterial, fresh-keeping and oil-proof starch film based on nanocellulose immobilized enzyme, characterized in that: The following steps are involved: S1. Preparation of antimicrobial agent: Mix citronellol, anthocyanin, chitosan, cinnamyl alcohol and menthol together, add starch, nano silver particles and quaternary ammonium salt in 2-3 times and mix together to obtain an antibacterial agent; S2. Preparation of mixture A: Absolutely dry starch and cationic starch are prepared into an aqueous solution of a certain concentration, heated in a 75°C water bath for gelatinization, polyvinyl alcohol is added and continued to be heated and stirred until completely dissolved, folic acid is added to the solution and reacted for 30 minutes, α-amylase is added to the solution and mixed evenly to obtain a mixture A, and the mixture A is divided into three parts; S3. Preparation of cellulose nanofibril immobilized pullulanase: Take CNF, the mass of which is 1.0%-10% of the mass of absolute dry starch, take pullulanase, the amount of which is 1U-10U per gram of absolute dry starch, mix CNF and pullulanase, and adjust the mixture with phosphate buffer to a pH value of 6, and shake the mixture with the adjusted pH value at a constant speed of 100-300rpm in a constant temperature air bath shaker at 30°C for 1-3 hours to complete the immobilization of pullulanase on cellulose nanofibrils, and obtain Pul@CNF complex; S4, cellulose nanofibril immobilized pullulanase system enzymatically hydrolyzes starch and adds tannic acid: Place the absolutely dry starch in a 250ml three-necked flask or a round-bottomed flask, add 50ml of distilled water to the flask, and place the flask in a 38°C water bath. Stir slowly to fully disperse the starch, and continue stirring for 5 minutes. Add the Pul@CNF complex prepared in step 1 and two portions of mixture A to the dispersed starch solution, and add water to a total volume of 100ml. Then slowly add tannic acid to the solution, continue stirring for 10 minutes, and heat to 95°C at a rate of 1°C / min. When the temperature reaches 95°C, add a plasticizer accounting for 40% of the absolute dry starch mass to the solution, and keep warm for 30 minutes while stirring. After stirring, remove bubbles from the obtained starch solution, and use a casting method to evenly spread the starch solution on an acrylic plate. Place the acrylic plate with the spread starch solution in a 50°C oven and dry for 8 hours. S5, antibacterial coating: After drying is completed, the composite starch film is torn off from the acrylic plate, MC and HPMC are dissolved in ethanol, heated to 65°C, and then PEG, epoxy soybean oil acrylate and water are slowly added to form a uniform transparent coating solution or gel, an antibacterial agent and a portion of mixture A are added to the coating solution or gel, and the coating solution or gel is applied to the composite starch film using a glass roller, and stored at a temperature of 25°C and a relative humidity of 50% for 48 hours to obtain a composite starch film containing curcumin.
2. The method for preparing the antibacterial, fresh-keeping and oil-proof starch film based on nanocellulose immobilized enzyme according to claim 1, characterized in that: The pH value of the phosphate buffer is 4-7.
3. The method for preparing the antibacterial, fresh-keeping and oil-proof starch film based on nanocellulose immobilized enzyme according to claim 1, characterized in that: The mass ratio of the starch to the antibacterial agent is 1:
3.
4. The method for preparing the antibacterial, fresh-keeping and oil-proof starch film based on nanocellulose immobilized enzyme according to claim 1, characterized in that: The ratio of the absolute dry starch to the cationic starch is 1:
1.
5. The method for preparing the antibacterial, fresh-keeping and oil-proof starch film based on nanocellulose immobilized enzyme according to claim 1, characterized in that: The added amount of the tannic acid is 1%-20%.
6. The method for preparing the antibacterial, fresh-keeping and oil-proof starch film based on nanocellulose immobilized enzyme according to claim 1, characterized in that: The cellulose nanofibrils are one or any combination of anionic, cationic, and neutral cellulose nanocrystals.
7. The method for preparing the antibacterial, fresh-keeping and oil-proof starch film based on nanocellulose immobilized enzyme according to claim 1, characterized in that: The plasticizer is one or any combination of glycerol, urea, ethylene glycol, polyethylene glycol, propylene glycol, sorbitol, and ethanolamine.
8. The method for preparing the antibacterial, fresh-keeping and oil-proof starch film based on nanocellulose immobilized enzyme according to claim 1, characterized in that: The ratio of citronellol, anthocyanidin, chitosan, cinnamyl alcohol and menthol is 1-2:3-4:1-2:0.5-1:1-1.
5.
9. The method for preparing the antibacterial, fresh-keeping and oil-proof starch film based on nanocellulose immobilized enzyme according to claim 1, characterized in that: The antibacterial agent and one portion of mixture A account for 1-10% of the total amount.
Citation Information
Patent Citations
A method for preparing a nano starch superhydrophobic coating
CN109235037B
Cited By
Antibacterial wear-resistant cellosilk and preparation method thereof
CN120330909A